2018
DOI: 10.7759/cureus.3656
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Gland Response to Vitamin D Deficiency in Type 2 Diabetes Mellitus: An Observational Study

Abstract: BackgroundStudies have linked vitamin D deficiency with the risk of type 2 diabetes mellitus (T2DM) and to the development of chronic complication of diabetes. Vitamin D receptors (VDR) have been found in many tissues in the body including the pancreas, a finding that indicates its role in insulin secretion. In addition, many studies have demonstrated the role of vitamin D and its receptor in insulin sensitivity and signal transduction. Vitamin D deficiency is common throughout the world, but not all vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
2
9
0
2
Order By: Relevance
“…Diabetes mellitus is manifested with abnormal bone mineral density (BMD), hyperglycemia, secondary calcium imbalance, disturbances in vitamin D [26], microvascular disease [27], and an increased risk of fall [28, 29]. With a high morbidity and mortality, it also adversely affects bone metabolism and increases the fracture risk [3032].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is manifested with abnormal bone mineral density (BMD), hyperglycemia, secondary calcium imbalance, disturbances in vitamin D [26], microvascular disease [27], and an increased risk of fall [28, 29]. With a high morbidity and mortality, it also adversely affects bone metabolism and increases the fracture risk [3032].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found reduced plasma vitamin D and calcitriol levels among T2DM individuals [49,50]. These studies have shown that impaired renal reabsorption of vitamin D binding proteins, impaired intestinal vitamin D absorption and increased sequestration of vitamin D by adipose tissue may be responsible for decreased plasma vitamin D and calcitriol concentrations in T2DM [39,43]. Furthermore, studies have shown that calcitriol production is impaired due to renal damage, low plasma PTH levels and PTH resistance in T2DM [47,51].…”
Section: Correlation Between Metabolic Parameters and Calciotropic Ho...mentioning
confidence: 99%
“…Previous research has shown increased concentrations of PTH and calcitonin in plasma of type 2 diabetic individuals [37,38]. According to studies the increased PTH concentration may have compensated for the increased calcium loss in urine and the increased plasma calcitonin concentration may have protected the body against the adverse effects of PTH oversecretion [13,39]. The harmful effects associated with elevated PTH secretion include hypercalcaemia and bone loss [23].…”
Section: Correlation Between Metabolic Parameters and Calciotropic Ho...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evre 2; Orta vitamin D eksikliğinde (25-OH vitamin D seviyesi <25 nmol/L ) parathormon seviyesinde %15-30 artış beklenir. Evre 3; ağır vitamin D eksikliğinde (25-OH vitamin D seviyesi <12,5 nmol/L) parathormon seviyesinde %30' dan fazla artış izlenmektedir (3). Şu anki verilere göre vitamin D düzeyi <20 ng/ml vitamin D eksikliği olarak tanımlanmaktadır (4).…”
Section: Introductionunclassified